Long Non-coding RNA LINC02474 Affects Metastasis and Apoptosis of Colorectal Cancer by Inhibiting the Expression of GZMB - Du, Tiantian; Gao, Qinglun; Zhao, Yinghui; Gao, Jie; Li, Juan; Wang, Lili; Li, Peilong; Wang, Yunshan; Du, Lutao; Wang, Chuanxin (Frontiers in Oncology, 2021)
Background Colorectal cancer (CRC) is one of the most frequently diagnosed malignancies. Metastasis is the main event that impedes the therapeutic effect on CRC, and its underlying mechanisms remain largely unclear. LINC02474 is a novel long noncoding RNA (lncRNA) associated with metastasis of CRC, while little is known about how LINC02474 regulates these malignant characteristics. Methods Expressions of LINC02474 and granzyme B (GZMB) were assessed by quantitative real-time polymerase chain reaction (qRT-PCR) or Western blotting analysis. Cell metastasis was detected by transwell assay and metastatic nude mouse model, and apoptosis was determined by Western blotting analysis and flow cytometry. Besides, the interaction between LINC02474 and GZMB was detected by dual-luciferase reporter assays. Results The expression of LINC02474 was significantly up-regulated in CRC tissues. Moreover, depletion of LINC02474 damaged the metastatic abilities of CRC cells in vivo and in vitro while boosting apoptosis. Besides, up-regulation of LINC02474 could promote migration and invasion, while apoptosis was inhibited in CRC cells. Besides, down-regulation of LINC02474 promoted the expression of GZMB, and interference of GZMB could increase the metastatic abilities of CRC cells while reducing apoptosis. Furthermore, LINC02474 was related to the transcriptional repression of GZMB in CRC cells determined by the dual-luciferase reporter assay. Conclusions The findings revealed that a novel lncRNA, LINC02474, as an oncogene, could promote metastasis, but limit apoptosis partly by impeding GZMB expression in CRC. Besides, LINC02474 had the potential to be used as a biomarker in the prognosis of CRC.